Report of an International Workshop on Preserving Historic Buildings of Major Importance - Sykora, David W.; Hynes, Mary E.; Karaesmen, Erhan (1993)
This report summarizes the activities and findings of an international workshop that focused on how recent advances in science and engineering may be exploited to evaluate the vulnerability of irreplaceable historic facilities to seismic hazards, to design remedial actions, and to develop an effective preservation methodology. The participants consisted of 28 professionals with expertise in the fields of seismology, geophysics, geotechnical and structural engineering, architecture, and art history. The workshop was held in Istanbul, Turkey, and included preservation-focused visits to the Mihrimah Mosque there and the Selimiye Mosque in Edirne. Products of the workshop included a procedural model for evaluating the threat to irreplaceable historic construction based on group findings from visits to the two mosques.